Mecanismos sociais da reforma agrária em SãO Paulo pelo viés etnográfico - Loera, Nashieli Rangel [UNESP] (FapUNIFESP (SciELO), 2015)
This article analyzes, from an ethnographic perspective, the configuration of social mechanisms that allows the production and achievement of land distribution policies in the State of São Paulo. Regarding on the dynamic and configuration of landless encampments of the MST in the Pontal de Paranapanema region I will demonstrate how cooperation relationship between State institutions as Itesp (Instituto de Terras do Estado de São Paulo), local governments and the MST are crucial in the process of State benefits distribution, in this case, a piece of land. This cooperation is part of the social conditions for the establishment of encampment forms as variations of a contemporary model of collective social demand.
Social mechanisms of agrarian reform in São Paulo
Keywords: Agrarian Reform; Encampment Time; MST; Social Mechanisms; State